2021
DOI: 10.1371/journal.pone.0252160
|View full text |Cite
|
Sign up to set email alerts
|

The epistemic roles of clinical expertise: An empirical study of how Swedish healthcare professionals understand proven experience

Abstract: Clinical expertise has since 1891 a Swedish counterpart in proven experience. This study aims to increase our understanding of clinicians’ views of their professional expertise, both as a source or body of knowledge and as a skill or quality. We examine how Swedish healthcare personnel view their expertise as captured by the (legally and culturally relevant) Swedish concept of “proven experience,” through a survey administered to a simple random sample of Swedish physicians and nurses (2018, n = 560). This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…For example, correlation plots show that proven experience is positively correlated with both science and personal experience but that personal experience is largely uncorrelated with science, reinforcing our interpretation (and the intention of the survey design) that by asking about both personal and proven experience in a population in which the latter is a well-known concept, the former would capture the strictly individual aspects of clinical experience. References Persson et al, 10 , 18 Wahlberg and Persson, 19 Wallin et al, 20 and Dewitt et al 21 describe studies focusing on the proven experience data of the survey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, correlation plots show that proven experience is positively correlated with both science and personal experience but that personal experience is largely uncorrelated with science, reinforcing our interpretation (and the intention of the survey design) that by asking about both personal and proven experience in a population in which the latter is a well-known concept, the former would capture the strictly individual aspects of clinical experience. References Persson et al, 10 , 18 Wahlberg and Persson, 19 Wallin et al, 20 and Dewitt et al 21 describe studies focusing on the proven experience data of the survey.…”
Section: Resultsmentioning
confidence: 99%
“…Refs. [19][20][21]. As proven experience is part of Swedish health care personnels' ideas on evidence, participants were also asked to respond to items on this concept.…”
Section: Scientific Background and Rationalementioning
confidence: 99%
“…However, a recent study by Dewitt et al. (2021) found that physicians, nurses and OTs primarily understand proven experience in terms of interventions/methods/etc.…”
Section: Science and Proven Experiencementioning
confidence: 99%
“…The difference between EBM and VBE is visible also within the integrative role. The integrative aspect is fundamental in EBM for implementation purposes ( Dewitt et al. 2021 ); the clinician needs to understand how to apply the evidence-based knowledge in a concrete case.…”
Section: Science and Proven Experiencementioning
confidence: 99%
See 1 more Smart Citation